Evaluation of Customer’s Perception for the Purchase of Apparel from Branded and Non-branded avenues: With Special reference to the State of Tamil Nadu - K.K. , Ramachandran (International Journal of Psychosocial Rehabilitation, 2020)
It is a well-known fact that the purchase behavior of a given consumer is being affected by a number of elements and these elements are supposed to affect the final purchase of the customer. As far as apparel are concerned they are related to the face value of the customer and important for public presence, hence a given customer is more conscious about the same. This present study investigates into the same parameters of customer choice and tries to identify the factors that are responsible for the same. The location of the study is Coimbatore city in Tamil Nadu. This present research is based on primary data and the respective size of the sample is 100 respondents. The method of sampling is convenience sampling and SPSS ver. 22.0 is used for the analysis of collected data. One way ANOVA is used to analyze the variance among the responses of the samples. The respective results of the present study will present a clear vision for the different components that are supposed to affect the behavior of the customer as far as apparel is concerned.